A simplified Johnson-Cook model of TC4T for aeroengine foreign object damage prediction. (15th June 2022) - Zhang, Hongbo; Hu, Dayong; Ye, Xubin; Chen, Xin; He, Yuhuai
Graphical abstract: Highlights: A simplified Johnson-Cook model with failure criterion of TC4T was developed through experiments and validated by numerical simulation. Laboratory simulated foreign object damage tests were carried out and compared with the predicted results. A full-scale 3D FE model of an aeroengine fan blade was developed by using the proposed Johnson-Cook model and the effects of pre-stress and impact position on FOD were discussed. Abstract: Foreign object damage (FOD) was one of the major concerns of airworthiness requirements for aeroengines in service and maintenance, which reduced the fatigue life and led to premature failure. In present work, dynamic mechanical properties of a new titanium alloy named TC4T were firstly investigated by using Split-Hopkinson pressure bar (SHPB) tests at high strain rates and quasi-static tensile tests with different triaxiality. Based on experimental data, a simplified Johnson-cook (J-C) model with failure criterion was established to describe the strain-rate dependent constitutive model for TC4T. Finite element (FE) models to simulate SHPB and quasi-static tensile tests were developed and validated by experimental results, respectively, to evaluate the effectiveness of the J-C model. Excellent agreements could be found between numerical prediction and experimental results. Secondly, laboratory simulated FOD tests were carried out by air gun to launch steel spherical projectiles with various diameters impacting the edge of the flat plate specimen made of TC4T at different impact velocities. The corresponding 3D FE model was also developed and predicted FOD profiles were compared with experimental results. Satisfactory agreement could be obtained between numerical predictions and the experimental measurements. Finally, a full-scale 3D FE model of an aeroengine fan blade was established by using the proposed J-C model to predict and evaluate FOD. The effect of the initial stress state and impact position on FOD were investigated and results showed that the initial stress had less influence on the sizes of FOD profiles, while the impact position had a significant effect on FOD.